Simple Lymphangioma of the Scrotum: A Case Report - Deng D; Niu M; Yang J; Deng L (Clinical, Cosmetic and Investigational Dermatology, 2022)
Dongmei Deng,1,* Mu Niu,1,* Jie Yang,1 Lijun Deng2 1Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, People’s Republic of China; 2Department of Dermatovenereology, Wuzhong People’s Hospital, Suzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Yang, Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, People’s Republic of China, Email 13337564169@163.com Lijun Deng, Department of Dermatovenereology, Wuzhong People’s Hospital, Suzhou, 215128, People’s Republic of China, Email 474974283@qq.comAbstract: As scrotal simple lymphangioma is a rare benign proliferation of lymphatic vessels in the scrotum, a few reports were documented. A 68-year-old man gradually developed vesicles on the scrotum for ten years and easily ruptured due to friction. Physical examination showed diffuse millet-sized vesicles on the scrotum with milky white fluids and chyle-like exudates. Histopathological examination revealed proliferating and dilated lymphatic vessels with various sizes of lumens in the dermis. An immunohistochemical study showed positive staining for D2-40 and CD31. Therefore, the patient was diagnosed with scrotal lymphangioma and received carbon dioxide laser therapy. After the treatment, the vesicles markedly decreased, and no apparent exudates were observed. During one year of the follow-up, no relapse, scars, or other complications occurred.Keywords: lymphangioma, scrotum, carbon dioxide laser